How Does a Photocatalytic Antimicrobial Coating Affect Environmental Bioburden in Hospitals?. (12th February 2018) - Reid, Matthew; Whatley, Vanessa; Spooner, Emma; Nevill, Alan M.; Cooper, Michael; Ramsden, Jeremy J.; Dancer, Stephanie J.
Abstract : BACKGROUND: The healthcare environment is recognized as a source for healthcare-acquired infection. Because cleaning practices are often erratic and always intermittent, we hypothesize that continuously antimicrobial surfaces offer superior control of surface bioburden. OBJECTIVE: To evaluate the impact of a photocatalytic antimicrobial coating at near-patient, high-touch sites in a hospital ward. SETTING: The study took place in 2 acute-care wards in a large acute-care hospital. METHODS: A titanium dioxide-based photocatalytic coating was sprayed onto 6 surfaces in a 4-bed bay in a ward and compared under normal illumination against the same surfaces in an untreated ward: right and left bed rails, bed control, bedside locker, overbed table, and bed footboard. Using standardized methods, the overall microbial burden and presence of an indicator pathogen ( Staphylococcus aureus ) were assessed biweekly for 12 weeks. RESULTS: Treated surfaces demonstrated significantly lower microbial burden than control sites, and the difference increased between treated and untreated surfaces during the study. Hygiene failures (>2.5 colony-forming units [CFU]/cm 2 ) increased 2.6% per day for control surfaces (odds ratio [OR], 1.026; 95% confidence interval [CI], 1.009–1.043; P =.003) but declined 2.5% per day for treated surfaces (OR, 0.95; 95% CI, 0.925–0.977; P <.001). We detected no significant difference between coated and control surfaces regarding S. aureus contamination. CONCLUSION: Photocatalytic coatings reduced the bioburden of high-risk surfaces in the healthcare environment. Treated surfaces became steadily cleaner, while untreated surfaces accumulated bioburden. This evaluation encourages a larger-scale investigation to ascertain whether the observed environmental amelioration has an effect on healthcare-acquired infection. Infect Control Hosp Epidemiol 2018;39:398–404